Synthesis of upconversion TiO2:Er3+-Yb3+ nanoparticles and deposition of thin films by spin coating technique. Issue 18 (15th December 2020) - Trabelsi, Fatma; Mercier, Frédéric; Blanquet, Elisabeth; Crisci, Alexandre; Salhi, Rached
Abstract: In this work, a simple, low temperature (T < 300 °C) procedure suitable to increase the efficiency of solar cell and optoelectronic devices through reducing the mismatch with solar spectrum in the infrared range is proposed. TiO2 co-doped with rare earth ions is a promising candidate for its use in optical field due to the possibility to expand the spectral absorption range. Here, pure and Er 3+ -Yb 3+ co-doped anatase-TiO2 nano-spherical particles (diameter < 50 nm) with high surface area (125.7 m 2 /g and 140.6 m 2 /g for the pure and co-doped, respectively), good crystallinity are prepared by hydrothermal-assisted sol-gel method, followed by their dispersion and deposition as thin films. The nanoparticles are characterized by studying their structural, morphology, surface chemical compositions and photoluminescent properties. From the dispersion study, results showed that the optimal conditions were obtained for co-doped TiO2 at operational pH = 3 and with 20 min as a suitable duration of ultrasonication. The co-doped TiO2 nanoparticles showed excellent upconversion properties (green and red emissions) at room temperature under 980 nm excitation. To extend this result towards optoelectronic and photonic applications, the upconversion nanoparticles are deposited at the surface of n-type (100) Si wafer using a spin-coating process. From scanning electron microscopy, it is observed that the entire surface of substrate is covered with a uniform film composed of compact arrangement of small nanoparticles with a good adhesion on Si surface, also the resulting 750 nm thick TiO2 :Er–Yb film maintained the upconversion luminescence phenomena.